Preliminary screening of alkaloids by using thin layer chromatography (tlc) analysis on selected fruit’s peels, in vitro roots of archidendron pauciflorum and eurycoma longifolia. / Nur Farah Izzati Yusri - Yusri, Nur Farah Izzati (2018)
Plant has been used to treat many diseases due to one of its compound contained which is alkaloids that exhibit many pharmacological effects. Since alkaloids has crucial effect on treating cancer diseases, this experiment is conducted by using the samples of selected fruit’s peels which are papaya (Carica papaya), banana (Musa acuminate), honeydew (Cucumis melo), watermelon (Citrullus lanatus) and dragon fruit (Hylocerous polyrhizus) and in vitro roots of Tongkat Ali (Eurycoma longifolia)and Djengkol beans (Archidendron pauciflorum). This experiment is conducted to detect the presence of alkaloids in all these samples, to identify which of the solvent ratio that can exhibit the best result and to compare the presence of alkaloids between fruit’s peels and in vitro roots. TLC is being applied in this experiments as it is inexpensive and easy for the separation of compound. The TLC method was performed with four differences ratio of running solvents which were 4:1, 3:2, 2:3 and 1:4. From this experiments it shows that Tongkat Ali contains many alkaloids compared to the Djengkol beans with the present of Unknown alkaloids A, B, C, D, E, H and 9-methoxycanthin-6-one with Rf value of 0.42, 0.53, 0.78, 0.84, 0.97, 0.92 and 0.83 respectively. While in Djengkol beans, the alkaloids that has been found were Unknown D and E with Rf value were 0.84 and 0.97 respectively. For fruit’s peels, peels of papaya, watermelon and Honeydew shows the higher present of alkaloids. The alkaloids present in papaya’s peels were Unknown I, J, K and R with Rf value of 0.28, 0.55, 0.92 and 0.66 respectively. Meanwhile, for the sample of banana’s peels, alkaloids that were present were Unknown L, M and N with Rf value of 0.62, 0.7 and 0.9 respectively. From honeydew’s peels, alkaloids present were Unknown O, P, Q and S with the Rf value of 0.25, 0.37, 0.48 and 0.96 respectively. For watermelon’s peels, alkaloids present were Unknown L, M, K and T with Rf value of 0.65, 0.7, 0.92 and 0.74 respectively. Dragon fruit’s peels has the present of alkaloids which was Unknown K with Rf value of 0.92. From four different ratio of solvent (Chloroform: Methanol), the ratio of 4:1 exhibit the best result. As conclusion, alkaloids were present in all these samples The ratio of 4:1 solvent exhibit the best result for both type of samples which were fruit’s peels and in vitro roots. From this experiments, all the results that has been obtained can be shared with others through the publication of journal.